Artificial Neural Network Modeling of Thermo-catalytic Methane Decomposition for Hydrogen Production - Alsaffar M.A.; Ghany M.A.R.A.; Ali J.M.; Ayodele B.V.; Mustapa S.I. (Springer, 2023)
Bayesian networks; Calcination; Catalysts; Knowledge based systems; Mean square error; Methane; Multilayer neural networks; Predictive analytics; Sensitivity analysis; Specific surface area; Topology; Artificial neural network modeling; Bayesian regularization; Calcination temperature; Catalytic methane decompositions; Coefficient of determination; Multi-layer perceptron neural networks; Non-linear relationships; Trained neural networks; Hydrogen production